PENGEMBANGAN PEMBELAJARAN E-LEARNING MATA KULIAH PTM/JALAN RAYA PENDIDIKAN VOKASIONAL KONSTRUKSI BANGUNAN FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA - Abdul Azis Mubarok; Riyan Arthur; Santoso Sri Handoyo (LPPM Universitas Negeri Jakarta, 2018)
Abstract This research is a development research that aims to develop learning especially in the form of E-Learning in PTM / highway courses. This development research is a Research and Development research method with Borg and Gall research model. This research is basically carried out through five main stages, namely Research and information gathering (Research and Information Collecting), planning, developing preliminary form of product, field testing and product revision (filed testing and product revision ), final product revision and disseminate and implementation processes. This research is only up to the Revision of the final product because it only reaches the development of E-Learning learning.This study uses a questionnaire as a tool to test the feasibility through validation of instructional experts, media experts and material experts and see respon from student The results of the development obtained E-Learning learning assessment products by instructional expert lecturers using a Likert scale score 1-4 get a score of 2.5 which is categorized as